55th AIAA/ASME/ASCE/AHS/ASC Structures, Structural Dynamics, and Materials Conference 2014
DOI: 10.2514/6.2014-0151
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Order Modeling for the Nonlinear Geometric Response of Some Joined Wings

Abstract: The focus of this investigation is on assessing the use of nonintrusive (i.e. developed directly from commercial finite element codes) nonlinear reduced order modeling techniques for the prediction of the strongly nonlinear response of joined wings, e.g. the snap-buckling they exhibit.A key component of the reduced order modeling is the selection of the basis to represent the response and this aspect will be extensively discussed leading to the formulation of new metrics for the assessment of the basis. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…A detailed investigation of the eigenvalues and eigvenvectors of the Nastran tangent stiffness matrix, its projection on the 38-mode basis, and of the 38-mode ROM tangent stiffness matrix, see [16] for a similar discussion, demonstrated that the 38-mode basis was not sufficiently rich to properly capture the changes in the dominant transverse modes shortly before, during, and after the mode switching transition. This issue was resolved (as in [16]) by enriching the basis with 3 POD eigenvectors of the residuals of the projection of the first and second eigenvectors of the Nastran tangent stiffness matrix on the 38-mode basis.…”
Section: Coupled Thermal-structural Rom Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…A detailed investigation of the eigenvalues and eigvenvectors of the Nastran tangent stiffness matrix, its projection on the 38-mode basis, and of the 38-mode ROM tangent stiffness matrix, see [16] for a similar discussion, demonstrated that the 38-mode basis was not sufficiently rich to properly capture the changes in the dominant transverse modes shortly before, during, and after the mode switching transition. This issue was resolved (as in [16]) by enriching the basis with 3 POD eigenvectors of the residuals of the projection of the first and second eigenvectors of the Nastran tangent stiffness matrix on the 38-mode basis.…”
Section: Coupled Thermal-structural Rom Resultsmentioning
confidence: 98%
“…This issue was resolved (as in [16]) by enriching the basis with 3 POD eigenvectors of the residuals of the projection of the first and second eigenvectors of the Nastran tangent stiffness matrix on the 38-mode basis. These latter eigenvectors were obtained in conditions close and after the mode switching transition.…”
Section: Coupled Thermal-structural Rom Resultsmentioning
confidence: 99%
“…However, results in this direction have not been quite encouraging. Some recent results are shown in references [9,10].…”
Section: Introductionmentioning
confidence: 91%
“…In the future, dynamic and aeroelastic analysis will be considered with the use on reduced models (comparison with the approach presented in Reference [48] will also be pursued). Further investigation needs to be performed for the best strategy for basis update.…”
Section: Recommendations and Further Researchmentioning
confidence: 99%